Problematika Proses Pemutakhiran Data Pemilih pada Pemilu Tahun 2024 - Zukni , Siti Delvira; Atmaja, Sudeno; Dila , Darma (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This research was conducted to find out the problems in the process of updating voter data in the 2024 elections in XYZ District. Updating voter data during elections is an important process to maintain the integrity and legitimacy of the electoral process. This process includes registering new voters, removing dead voters, and updating voter data with changes in address or identity. Of course, in updating election data, many problems often arise during elections in various countries. Updating of incorrect or inaccurate data can have a significant impact on the integrity and public confidence in election results. In the process of updating the data there is matching and research or what is often called Coklit. Matching and Research (Coklit) is an important step in the process of updating voter data in general elections in many countries. Before registering as a voter, it is necessary to update voter data. Updating voter data is the process of updating and correcting information on voter lists or fixed lists of voters in the context of general elections or other general elections. Updating voter data aims to ensure that the voter list is accurate and that the number of voters entitled to vote is correct. Several steps were taken in updating voter data, including compiling the KPU voter list and submitting it to PPS, matching and research, preparing voter lists that were updated by PPS and making summaries at the village/kelurahan level and submitting them to the KPK. The method the author uses is qualitative, namely research that is descriptive in nature and tends to use analysis. To obtain data, this research method conducted interviews with informants, by studying documentation related to the research focus.